The educational value of the multi-disciplinary meeting (MDM) in surgical oncology: A systematic review and thematic content analysis. Issue 5 (May 2022) - Temperley, Hugo; Waters, Caitlin; Larkins, Kirsten; Murray, Cian; O'Sullivan, Niall J.; Mockler, David; Humm, Gemma; Norden, Catriona; Phoenix, Eimear; Donohoe, Claire L.; Warrier, Satish; Mohan, Helen
Abstract: Multidisciplinary meetings are an important part of cancer care and surgical planning. However, there is also an important educational role of MDMs in training the next generation of surgical oncologists. This systematic review (SR) aimed to examine the current educational role of the surgical oncology MDM and identify areas for improving educational value. Medline, OVID, EMBASE, CINHIL and Web of Science were searched using a predefined search strategy in keeping with the PRISMA statement. Data was analysed and synthesized in narrative format and thematic content analysis was performed. Three main groups of studies were identified, those with: 1. A simulated non-clinical MDM (3/13), 2. clinical MDMs with a defined educational intervention (1/13) and 3. observational studies that described the educational benefit of the clinical MDM with no intervention (9/13). Satisfaction rates were high and learning outcomes improved where an intervention to improve the educational content of the MDM had been implemented(simulated or non-simulated). Respondents considered the MDM a valuable tool for learning non-technical skills and training surgical oncologists and medical students. Using defined interventions e.g. debriefing post MDM, or simulation can improve the educational benefit for learners. Qualitative analysis identified clinical knowledge, decision making and the acquisition of non-technical skills as the key themes within included studies.